Human variants of O(6)-alkylguanine-DNA alkyltransferase - Pegg, Anthony E. (2007)
This article summarizes the current understanding of known variant forms of the MGMT gene that encode an altered protein. Epidemiological studies have been carried out to test whether these alterations are associated with altered cancer risk. Laboratory studies using recombinant proteins and cells expressing the known variants have investigated the possible effects of these sequence alterations on the ability of the encoded O(6)-alkylguanine-DNA alkyltransferase protein to protect cells from alkylation damage and to respond to therapeutic inactivators currently undergoing trials for cancer chemotherapy.